Analisis Pengelolaan Piutang dengan Menggunakan Receivable Turnover dan Average Collection pada Koperasi Republik Mitra Amanah Periode Tahun 2016-2018: - - Wakhid Yuliyanto (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
This study aims to determine the financial performance using the analysis method of calculating the average of accounts receivable, accounts receivable turnover, and ACP. The study used quantitative descriptive methods. The results of this study indicated that the average accounts receivable period 2016-2017 had increased 10%, while period 2017-2018 decreased 2,0%. Accounts receivable turnover period 2016-2018 had increased 0.56 times and 0.02 times. ACP in 2016 was 34 days and 2017-2018 had dropped to 32 days. Financial Statements of the Koperasi Republik Mitra Amanah had a total value of 80 and it was considered good. Based on the results of these calculations, these could be concluded that although the financial report was good in Koperasi Mitra Amanah, but the financial performance in Koperasi Mitra Amanah was in a bad condition, it because of the imbalances financial between expenditure and income of the cooperative.